Digital skills and information processing from a child's perspective - Flor Heydi Chaves Barquero; Maricarmen Cantú Valadez; Catalina María Rodríguez Pichardo (Universidad Autónoma de Baja California, 2016)
This study responds to the need to determine whether, in an educational setting that incorporates Information and Communication Technology (ICT) and a project-based learning approach, 68 fourth-, fifth- and sixth-grade students from a public institution in Costa Rica have acquired the digital, information processing and teamwork skills necessary to face the challenges of the knowledge society we live in. The study was developed from a mixed embedded, mainly quantitative approach which was exploratory in scope. The results show a medium-high level of performance for digital skills (3.93) and information processing (3.82); and a high performance for teamwork skills (4.17) on a scale of 1 to 5, 5 being the highest score. It is concluded that, due to the age of the population, the results are not definitive, and further training in these skills is recommended.